Developing Digital English Materials Based on Contextual Teaching Learning for Economics Students - Imam Fauzi; Yayat Ruhiat; Lukmanul Hakim (Loquen, 2021)
This study refers to the problem study of the teaching and learning needs which requires English learning resources in order to meet the expectations of students during the ESP pandemic teaching and learning process. The fundamental goal of this research is to create effective digital English learning resources for students at the University of Serang Raya's Economics faculty. The main goals of creating a digital English coursebook based on contextual teaching-learning are to help Economics students enhance their English language skills and to meet their learning demands. This research was carried out using the PSDD model as a research and development method (Preliminary Study, Design, and Develop). The information is gathered using a questionnaire and a speech assessment form.